El papel de la política industrial en el cambio tecnológico del sector manufacturero en México, 1993-2020 - Rodríguez Zavala, Claudia Paulina (Universidad Michoacana de San Nicolas de Hidalgo, 2024)
The objective of this research is to understand the performance of technological change in the 9 divisions of the manufacturing sector in Mexico during the period 1993-2020. The calculation of technological change was obtained based on the proposal of Kumbhakar and Lovell (2000), using the stochastic frontier method, calculated from data obtained from the National Accounts System page of INEGI, LA KLEMS model with a 2013 base year. The results indicate that technological change exhibits heterogeneous behavior among the 9 divisions, with Division V (chemicals, petroleum derivatives, rubber, and plastic products), Division VII (basic metal industries), and Division VIII (metal products, machinery, and equipment) showing the best performance, while Division I (food, beverages, and tobacco industry) and Division III (wood industry) demonstrated the lowest performance. Division V emerges as the most dynamic industry, maintaining sustained growth throughout the study period. Based on the analysis of the results, a comprehensive public policy proposal is presented to promote technological change within the framework of the nearshoring phenomenon.

El objetivo de esta investigación es conocer el desempeño del cambio tecnológico en las 9 divisiones del sector manufacturero en México durante el periodo 1993-2020. El cálculo del cambio tecnológico se obtuvo a partir de la propuesta de Kumbhakar y Lovell (2000), por medio del método de frontera estocástica, calculada a partir de los datos obtenidos de la página del Sistema de Cuentas Naciones de INEGI, modelo LA KLEMS año base 2013. Los resultados obtenidos indican que el cambio tecnológico muestra un comportamiento heterogéneo entre las 9 divisiones, manteniendo el mejor desempeño la división V (sustancias químicas, derivados del petróleo, productos de caucho y plástico), la división VII (industrias metálicas básicas) y la división VIII (productos metálicos, maquinaria y equipo); mientras que el desempeño más bajo se presentó en la división I (industria alimentaria, bebidas y tabaco) y la división III (industria de la madera). La industria más dinámica es la V, manteniendo durante el periodo de estudio un crecimiento sostenido. A partir del análisis de los resultados se hace una propuesta de política pública integral, para favorecer el cambio tecnológico enmarcado en el fenómeno del nearshoring.
Instituto de Investigaciones Económicas y Empresariales. Maestría en Políticas Públicas
Keywords: info:eu-repo/classification/cti/5; ININEE-M-2024-0228; Cambio tecnológico; Frontera estocástica; Política industrial; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/18592